2018
DOI: 10.1074/jbc.m117.811240
|View full text |Cite
|
Sign up to set email alerts
|

Topical mevastatin promotes wound healing by inhibiting the transcription factor c-Myc via the glucocorticoid receptor and the long non-coding RNA Gas5

Abstract: Diabetic foot ulcers (DFUs), a life-threatening complication of diabetes mellitus, have limited treatment options, often resulting in amputations. HMG-CoA reductase inhibitors such as statins are cholesterol-reducing agents that may provide a new therapeutic option. Statins target the cholesterol pathway and block the synthesis of the wound-healing inhibitors farnesyl pyrophosphate (FPP) and cortisol, ligands for the glucocorticoid receptor (GR). Here we demonstrate that the naturally occurring statin mevastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…GAS5 played significant roles in diverse cellular processes through mediating cell cycle, apoptosis, autophagy, drug resistance, or inflammatory response . Since GAS5 is located both in nuclear and cytoplasm, it exerts molecular mechanisms by acting as riborepressor to block the activation of target gene transcription (eg, c‐Myc) . Also, it can function as a ceRNA through different signaling axes (eg, miR‐222/PTEN/Akt/mTOR and miR‐21/PTEN/MMP‐2), modulates gene transcription via interacting with transcriptional factors (eg, E2F1), or directly controls gene translation (eg, NS3) .…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 played significant roles in diverse cellular processes through mediating cell cycle, apoptosis, autophagy, drug resistance, or inflammatory response . Since GAS5 is located both in nuclear and cytoplasm, it exerts molecular mechanisms by acting as riborepressor to block the activation of target gene transcription (eg, c‐Myc) . Also, it can function as a ceRNA through different signaling axes (eg, miR‐222/PTEN/Akt/mTOR and miR‐21/PTEN/MMP‐2), modulates gene transcription via interacting with transcriptional factors (eg, E2F1), or directly controls gene translation (eg, NS3) .…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested that deletion of the Sp1-binding site in the promoter region of GAS5 leads to downregulation of GAS5 expression, thereby inhibiting apoptosis and resulting in autoantigen exposure and the production of autoantibodies. 27,28,71 Researchers have found that the silencing of nuclear enriched abundant transcript 1 (lncRNA NEAT1) can significantly reduce the expression of a group of chemokines and cytokines, including interleukin 6 (IL-6) and CXCL10. NEAT1 expression is induced by lipopolysaccharide via activation of p38 and is higher in the peripheral blood cells of SLE patients than in healthy individuals.…”
Section: Lncrnas and Human Autoimmune Diseasesmentioning
confidence: 99%
“…Further research found that Gas5 binds to the DNA‐binding domain of GR by acting as a decoy GRE, thus competing with DNA GREs for binding to GR. The study suggested that deletion of the Sp1‐binding site in the promoter region of GAS5 leads to downregulation of GAS5 expression, thereby inhibiting apoptosis and resulting in autoantigen exposure and the production of autoantibodies …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
“…The activation of GR by cortisol or FPP caused nuclear translocation of β-catenin, leading to induction of c-myc, a hallmark of chronic nonhealing wounds. This led to the proposal to use statins to restore epidermal homeostasis as targeting the cholesterol pathway interferes with the production of FPP and cortisol, resulting in substantial reduction of GR activation, and c-myc downregulation [89]. It has also been shown that GCs can also inhibit keratinocyte migration and wound healing by activation of nongenomic signaling pathways involving membrane GR regulation of phospholipase C/protein kinase C ultimately activating β-catenin and c-myc [90].…”
Section: Keratinmentioning
confidence: 99%